2019
DOI: 10.1038/s41598-019-46250-4
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of tight junctional localization of a claudin-16 mutant D97S by antimalarial medicine primaquine in Madin-Darby canine kidney cells

Abstract: Magnesium ion (Mg 2+ ) is paracellularly reabsorbed through claudin-16 (CLDN16) in the thick ascending limb (TAL) of Henle’s loop in the kidney. Genetic disorders of CLDN16 cause mislocalization of CLDN16, resulting in hypomagnesemia. There is no effective treatment for hypomagnesemia except for magnesium administration. Here, we searched for a novel drug to restore tight junctional localization of a CLDN16 mutant. A D97S mutant, which has a mutation in the first extracellular loop (ECL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…When heterologously expressed in epithelial cells, CLDN16 has varied effects, 109–114 depending on the experimental model (see Ref. 71 for a review).…”
Section: Paracellular Renal Tubular Transport Of Magnesiummentioning
confidence: 99%
See 1 more Smart Citation
“…When heterologously expressed in epithelial cells, CLDN16 has varied effects, 109–114 depending on the experimental model (see Ref. 71 for a review).…”
Section: Paracellular Renal Tubular Transport Of Magnesiummentioning
confidence: 99%
“…When heterologously expressed in epithelial cells, CLDN16 has varied effects, [109][110][111][112][113][114] affects Mg 2+ reabsorption is also unclear as a lower Mg permeability was reported when CLDN19 is expressed in MDCK II Tet-Off and LLC PK1 cells. 96,110 In analyses of recombinant proteins, CLDN16 and CLDN19 interact to form a cis heterodimer.…”
Section: Cldn16 and Cldn19mentioning
confidence: 99%
“…Blocking clathrin-mediated endocytosis increases surface expression of some CLDN16 mutants in vitro. Primaquine, an antimalarial agent increases also cell surface localization of a CLDN16 mutant in vitro [83].…”
Section: Prognosis and Treatmentmentioning
confidence: 99%
“…Some investigators found that claudin 16 increases transepithelial transport of Ca 2+ [129] and of Mg 2+ [83,130,131], when heterogously expressed in epithelial cells (Table 6). Others found an effect of CLDN16 only on Mg 2+ (not Ca 2+ ) permeability [48].…”
Section: Variants/pathogenesismentioning
confidence: 99%